2019
DOI: 10.6118/jmm.19200
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Multi-Dimensional Group Counseling Program Based on the GATHER Approach on the Quality of Life in Surgically Menopausal Women

Abstract: Objectives: Surgical menopause can influence women's quality of life in many aspects. This study was designed to assess the effectiveness of a multi-dimensional group counseling program based on the great clients, ask clients, tell clients, help clients, explain how to use, return for follow up (GATHER) approach, on quality of life in the surgically menopausal women. Methods: This randomized clinical trial was conducted using two groups. The study comprised 78 women meeting inclusion criteria who had visited 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The GATHER model is a counseling model that can be used both individually, and in groups 21 . Various studies have shown the positive effects of this model in the field of women's health 22-25 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The GATHER model is a counseling model that can be used both individually, and in groups 21 . Various studies have shown the positive effects of this model in the field of women's health 22-25 …”
mentioning
confidence: 99%
“…21 Various studies have shown the positive effects of this model in the field of women's health. [22][23][24][25] Considering that the transition to menopause and the symptoms that women experience during this period harm women's physical and mental health and can reduce women's quality of life, 16 finding effective ways to improve their quality of life is one of the duties of health care providers. Among healthcare providers, midwives have an important role in counseling and health education for women, the family, and the community.…”
mentioning
confidence: 99%